Pemanfaatan Ubi Jalar Menjadi Pakan Ikan Lele di Desa Sindang Karya, Kecamatan Menes, Kabupaten Pandeglang - Encep Andriana; Indhira Asih Vivi Yandari; Ratna Sari Dewi; Callista Aulina; Tri Esti Noviyanti; Suci Ramadayanti; Ila Maratush Shalihah (Jurnal Pengabdian Pada Masyarakat, 2021)
UTILIZATION OF SWEET POTATOES AS CATFISH FEED IN SINDANGKARYA VILLAGE, MENES DISTRICT, PANDEGLANG REGENCY. Sweet potatoes have the potential to be made into various processed, one of which is a source of carbohydrates in fish-feed. Every day there is an increase in the fish feeds' price without an increase in the selling price of cultivated fish, which is a problem faced by fish cultivators. So, the search for alternative feeds, namely natural feed that is cheap and easy to find, continues to be conducted to reduce production costs. Moreover, to reduce costs, the protein sources for feed are utilizing the cheap local raw materials of snail meat flour. This activity is expected to motivate the growth of independent fish feed groups from local raw materials and provide knowledge to the community to utilize village natural resources into products with selling value, in order to improve the community welfare. The activity begins with the first stage of activity preparation, the preparation of raw feed materials, coordination with the village and presenters, and schedule preparation. The second stage is socialization or counseling to villagers about the benefits of making fish feed independently and the stages of making catfish feed made of sweet potatoes and snails that contains good nutritional by Lecturer of the Fisheries Science Study Program, Muh. Herjayanto, S.Pi., M.Si. The third stage is training for Sindangkarya Villagers in making the fish feed made from sweet potato flour and snail flour independently accompanied by lecturers and students. Community service activities conducted in Sindangkarya Village can be said to have enough participation from the local community. A good response is shown by the counseling process that has run smoothly and actively asking questions, so the process of making fish feed made from sweet potato flour and snail flour can run well.